The finite element method for MHD flow at high Hartmann numbers - Nesliturk, AI; Tezer-Sezain, M (Elsevier Science Sa, 2005)
A stabilized finite element method using the residual-free bubble functions (RFB) is proposed for solving the governing equations of steady magnetohydrodynamic duct flow. A distinguished feature of the RFB method is the resolving capability of high gradients near the layer rep-ions without refining mesh. We show that the RFB method is stable by proving that the numerical method is coercive even not only at low values but also at moderate and high values of the Hartmann number. Numerical results confirming theoretical findings are presented for several configurations of interest. The approximate solution obtained by the RFB method is also compared with the analytical solution of Shercliffs problem. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: MHD flow; stabilized FEM